The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14411/eje.2014.062
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development in a lepidopteran with variable instar number, Pseudocoremia suavis (Geometridae), under standard rearing conditions and when parasitised by Meteorus pulchricornis (Hymenoptera: Braconidae)

Abstract: Growth and development in a lepidopteran with variable instar number,Abstract. Though extra instars are often associated with poor conditions and thought to be a compensation for a low growth rate, the reasons why they are necessary, and for variable instar number existing under standard rearing conditions, are not yet clear. In standard rearing conditions, approximately half of Pseudocoremia suavis larvae had five instars (Type I larvae), and half six instars (Type II larvae). Type II larvae took longer to pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…For instance, Barraclough et al . noted that growth in the geometrid moth, Pseudocoremia suavis , fell into two classes depending on instar number (5 or 6) and these classes were independent of sex 14 . In this case, the 6 instar larvae took longer to pupate but had shorter larval durations at the 3–5 instar stage, and changes in instar number likely represented a plastic response to different growth conditions and the need for larvae to reach a particular size for pupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Barraclough et al . noted that growth in the geometrid moth, Pseudocoremia suavis , fell into two classes depending on instar number (5 or 6) and these classes were independent of sex 14 . In this case, the 6 instar larvae took longer to pupate but had shorter larval durations at the 3–5 instar stage, and changes in instar number likely represented a plastic response to different growth conditions and the need for larvae to reach a particular size for pupation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, instar number variation may reflect a genetic polymorphism in cases where variation in instars expressed under constant conditions occurs regardless of sex 12 . Variation in instars may also be unrelated to sex and genetic factors and represent a genetically fixed adaptive strategy; instar variability might serve to produce larvae with a range of emergence times to spread risk associated with emergence under unpredictable unfavorable periods, allowing organisms to hedge their bets 9 13 14 .…”
mentioning
confidence: 99%
“…Protein and carbohydrate ratios affected the survival and development of Henosepilachna vigintioctopunctata F. larvae (Coleoptera: Coccinellidae) (Wang et al 2018). Barraclough et al (2014) showed that the increase in the number of Pseudocoremia suavis Butler larvae instars was related to poor nutritional conditions, and more larval instars were needed for pupal emergence. Similar findings on the larvae of Orgyia antiqua (L.) (Lepidoptera: Erebidae) were reported by Esperk and Tammaru (2010).…”
Section: Biological Characteristics Of D Frumentimentioning
confidence: 99%
“…Most of the host caterpillars are leaffeeding herbivores, but this also successfully parasitizes grain feeders (Ephestia kuehniella Zeller) and wax feeders (Galleria mellonella (L.)) (Lepidoptera: Pyralidae) in the laboratory (Table 1). Whereas a wide range of host instars are acceptable, intermediate instars seem to be the best suited for parasitism (Barraclough et al 2014;Fuester et al 1993;Liu andLi 2006, 2008;Liu et al 2013;Malcicka and Harvey 2014;Zhang et al 2014).…”
Section: Does Cocoon Suspension Offer Protection Against Hyperparasitmentioning
confidence: 99%